Evaluasi Berdasarkan Pemahaman Teologi Injil Sinoptik terhadap Kristologi dalam ‘The Davinci Code’ - Epafras Mujono; Sri Wahyuni (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
This study is an evaluative descriptive study, in particular the concept of Christology in 'The Davinci Code'. The research method is descriptive research that aims to describe (explain, describe) data. And evaluative mean to be giving an evaluation of the circumstances or specific data. So this study will provide an explanation at the same time give an assessment (evaluation) of the data (Christology in The Da Vinci Code) using data Sinotik Gospel. This research has a purpose: First, to explain the ideology. Christology contained in The Da Vinci Code. Second, to present an evaluation of Christology contained in The Da Vinci Code, based on the teachings of Christology in the Synoptic Gospels. The scope of this article are: Firstly, this study only discusses the fundamental Christological contained in The Da Vinci Code. Second, the data used to evaluate Christology in The Da Vinci Code is only the data of the Synoptic Gospels.